2022
DOI: 10.1007/s12072-022-10369-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis: impact of anti-viral therapy on portal hypertensive complications in HBV patients with advanced chronic liver disease

Abstract: Background:The efficacy of treatment with nucleos(t)ide analogues (NAs) in non-cirrhotic chronic hepatitis B (CHB) patients is well-established. However, its impact on complications of portal hypertension in advanced chronic liver disease (ACLD) is less well-characterized.Methods: MEDLINE/PubMed, EMBASE, Web of Science, Cochrane Central Register of Controlled Trials, and abstracts of major international hepatology meetings were searched for publications from Jan 1, 1995 to Nov 30, 2021. Randomized control tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Nonetheless, they found that long-term AVT significantly decreases the risk of hepatic decompensation. Similarly, further studies regarding the liver-related prognosis of patients with HBV-related LC with long-term AVT should be implemented to establish the management of the high-risk patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they found that long-term AVT significantly decreases the risk of hepatic decompensation. Similarly, further studies regarding the liver-related prognosis of patients with HBV-related LC with long-term AVT should be implemented to establish the management of the high-risk patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high serum HBV-DNA levels are at a higher risk of developing liver cirrhosis, hepatic decompensation, and HCC 1,2. Long-term AVT using entecavir or tenofovir disoproxil fumarate is regarded as the current mainstay of managing patients with chronic HBV infection 3–8. Nevertheless, as potent AVT cannot eradicate intrahepatic HBV, periodic surveillance to detect HCC at an early stage is still required 3,4,9–14…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Long-term AVT using entecavir or tenofovir disoproxil fumarate is regarded as the current mainstay of managing patients with chronic HBV infection. [3][4][5][6][7][8] Nevertheless, as potent AVT cannot eradicate intrahepatic HBV, periodic surveillance to detect HCC at an early stage is still required. [3,4,[9][10][11][12][13][14] To date, there are significant discrepancies among practice guidelines regarding the management of patients with compensated cirrhosis with LLV, defined as a serum HBV-DNA level of 20-2000 IU/mL.…”
Section: Introductionmentioning
confidence: 99%